Noncovalent Interactions in SIESTA Using the vdW-DF Functional: S22 Benchmark and Macrocyclic Structures - Carter, Damien; Rohl, Andrew (American Chemical Society, 2012)
We investigate the performance of the vdW-DF functional of Dion et al. implemented in the SIESTA code. In particular, the S22 data set and several calixarene-based host–guest structures are examined to assess the performance of the functional. The binding energy error statistics for the S22 data set reveal that the vdW-DF functional performs very well when compared to a range of other methods of treating dispersion in density functional theory, and to vdW-DF implementations in other codes. For the calixarene host–guest structures, the structural properties and binding energies are compared to previous experimental and computational studies, and in most cases we find that vdW-DF provides superior results to other computational studies.